Comparison of yield, cost, and sensory characteristics of whole versus dressed bangus (Chanos chanos) for institutional use - Perdigon, Grace P.
The study was designed to compare the yield, labor time,raw food and labor costs, and sensory characteristics of whole and of dressed bangos prepared as Bangos Pinangat and as Bangos Frio in large quantity production. The yield of 120 kgs., as purchased, of whole and of dressed bangos were determined in terms of number of fish, number of serving portions, and total weight of edible portion. Labor time was determined by recording the man-minutes spent in processing fish from the tme the fish was brought to the preparation unit until it was ready for use in a recipe. Processing of whole bangos includes scaling, cutting, eviscerating, and final washing. For dressed bangos, processing included cutting and final washing.The cost of labor spent in the preparation of each form of fish was based on the number of man-hour spent in the preparation activities multiplied by the hourly wag of each worker. In the analysis of date, man-minutes was converted to man-hours. Raw food cost of each form of bangos was determined by multiplying the quantity of fish purchased by its unit cost.Total unit cost of either forms of fish was determined by adding food cost to labor cost. A difference test and an acceptability test were administered to evaluate the sensory characteristics of Bangos Pinangat and of Bangos Frito prepared from whole and from dressed fish. A difference test employing the triangle method was administered to a panel of ten. An acceptability test using the hedonic scale was administered to the panel and to an average of 209 customers in the dining rooms of the hospital. One hundred and twenty kilograms, as purchased, of dressed bangos had a higher yield the the same amount of whole bangos in the number of fish and number of serving portions by 11 percent. the edible portion weight of dressed bangos was higher by eight percent for the same amount of whole bangos. the Total preparation time of whole bangos was longer than 6.75 hours or 15 percent than hat of the same amount of dressed bangos. The cost of labor for the same amount of dressed bangos was more than that for the same amount of dressed bangos by P9.25 (based on the VMH contract price of bangos at the time of data collection, the cost of whole bangos was cheaper than that of dressed by P48.00 or 11.76 percent. The combined raw food and labor costs of 120 kgs., A.P., of whole bangos was cheaper by P38.64 or 9 percent than that of the same amount of dressed bangos.The foregoing cost comparison of whole and of dressed bangos were based on the same purchased weight of both forms of fish but with varying yields. To make a meaningful cost comparison of both forms of fish, cost were determined for 1,200 serving portions. This is the average number of serving portions served per meal at the VMH/ It as found that for 1,200 serving pattern of each form fish, the total preparation time of whole bangos would be longer than that for dressed bangos by 7.5 hours (70 percent)Thus, the labor cost of whole bangos would be higher by P10.27 (77percent)than that for dressed bangos. The raw food cost of the same number of serving portions of dressed bangos would be more expensive than that for whole bangos by P3.15 (0.7 percent. The combined raw food and labosr cost of 1200 servings of whole bangos would be higher also than that of the same number of serving of dressed bangos by 7.12 or 1.5 percent. This reveals that for the same number of serving portions the savings in raw food cost by using whole bangos for institutional use does not affect the higher cost incurred in the preparation of dressed bangos. Panel rating for odor, flavor, texture, and acceptability of Bangos Pinangat and Bangos frito prepared from whole fish were significantly higher (at five percent) than those of menu items prepared from dressed fish. Menu items prepared from whole fish had "fresh sea-weed odor" whereas menu items prepared from dressed had "fishy odor". In Addtion, menu itmes prepared from whole fish had " pleasant fish flavor" as compared to the "mild fish flavor" of the prepared from dressed fish. Bangos Pinangat and Bangos frito prepared from whole fish had "firm, not dry" texture while these prepared from dressed were "firm, dry" in texture. Panel ratings for acceptability of menu itms prepared form whole fish were significantly higher (five percent) than those of menu items prepared from dressed. The panel members "like very much' the menu items prepared from whole but "like slightly" those prepared from dressed. However, consumer ratings for acceptability of Bangos Pinangat and Bangos frito prepared from whole fish were not significantly different from those prepared from dressed fish. The consumers "like slightly" both menu items prepared from either form of fish.